TECTONIC MOVEMENTS, SEISMICALLY ACTIVE AND EARTHQUAKE GENERATING LAYER OF THE CONTINENTAL LITHOSPHERE - Levi K.G. (My University, 1988)
There is reason to think that the origin of the seismoactive (focal) layer is determined by deformation of an earthquake-generating layer of large volume. The earthquake-generating layer includes not only the part of the lithosphere in which earthquake foci are concentrated, but also that whole part of the lithosphere which, upon being deformed, can fail and generate seismic events. As a result of deformation, and more precisely, as a function of the rate of deformation, the earthquake-generating layer can fail at different depths. For comparison with the rate of the tectonic movements it is expedient to use the S/Le ratio, which makes it possible simultaneously to take into account the character of changes in thickness of seismically active and earthquake-generating layers of the continental lithosphere, resulting from tectonic processes. Comparison of the S/Le and V indicates that there is a stable relationship between them. It is assumed that the energy capacity can be approximately characterized by maximum magnitudes M of the instrumentally registered earthquakes in a seismically active layer of thickness S, it can be presumed that there would be an empirical relationship between M and S/Le. Equations are given that can be used for regional constructions and seismological analyses only in the USSR, where the determinations of earthquake foci and their energy has been standardized.